The Privileged Playgoers of Shakespeare's London, 1576-1642 - Cook, Ann Jennalie, 1934-2017 (Book collections on Project MUSE., 1981)
Besides documenting the predominant presence of privileged patrons in the audience, the author discusses the shape of the privileged life, the place of the privileged in the social structure, the forces that drew so many of them to London, and the factors that made them such avid theatergoers. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.